Gender differences in attentional processes and attractiveness evaluation models during gait observation - Tanabe, Hiroko; Yamamoto, Kota (Frontiers in Psychology, 2025)
IntroductionPhysical attractiveness plays a crucial role in building interpersonal relationships and in daily communication. Attractiveness is perceived through nonverbal information regarding one’s morphological features, posture, movement, and behavior. Selective pressures throughout our species’ evolutionary history have shaped sex differences in the evaluation of physical attractiveness. However, research on the process of body attractiveness perception has been limited to static information involving body images. Therefore, a better understanding of the attractiveness perception process in the real world requires an appreciation of the attractiveness perception mechanism of physical movement.MethodsThis study examined the attractiveness perception of 30-s walking animations, as well as gender differences in gaze behavior and statistical models of attractiveness evaluation. We recruited 16 men and 17 women and made gender comparisons of fixation ratio to each gaze area (head, trunk, hip, leg, and others). Furthermore, the standardized estimates of the statistical models were qualitatively compared between male and female observers.ResultsMale observers were highly fixated on the walkers’ trunk, whereas female observers tended to shift their attention from the trunk to the legs, especially when observing high-preference animations. The statistical model for attractiveness evaluation, which used gait parameters for each gender, showed the tendency that when assessing attractiveness, male observers placed greater weight on the walkers’ trunk silhouette, whereas female observers prioritized parameters requiring whole-body observation.DiscussionGender differences in gaze behavior were observed in the assessment and perception of human movement attractiveness; such differences may reflect the evaluation model for each gender. The results suggest that men assess female gait attractiveness based on observations of the reproductive regions of the female body. In contrast, women perceive other women as potential competitors and assess female gait attractiveness based on beauty standards, which are shaped by sociocultural environments and the walker’s psychological state. Our findings are the first step toward understanding the process of perceiving the attractiveness of physical movement and are expected to help generate attractive biological motions.